Family-group names of fossil fishes - van der Laan, Richard (European Journal of Taxonomy, 2018)
The family-group names of animals (superfamily, family, subfamily, supertribe, tribe and subtribe) are regulated by the International Code of Zoological Nomenclature. Particularly, the family names are very important, because they are among the most widely used of all technical animal names. A uniform name and spelling are essential for the location of information. To facilitate this, a list of family-group names for fossil fishes has been compiled. I use the concept ‘Fishes’ in the usual sense, i.e., starting with the Agnatha up to the †Osteolepidiformes. All the family-group names proposed for fossil fishes found to date are listed, together with their author(s) and year of publication. The main goal of the list is to contribute to the usage of the correct family-group names for fossil fishes with a uniform spelling and to list the author(s) and date of those names. No valid family-group name description could be located for the following family-group names currently in usage: †Brindabellaspidae, †Diabolepididae, †Dorsetichthyidae, †Erichalcidae, †Holodipteridae, †Kentuckiidae, †Lepidaspididae, †Loganelliidae and †Pituriaspididae.